Homogenization of Mammalian Tissues - John Graham (The Scientific World Journal)
Satisfactory homogenization of a tissue is a necessary prerequisite to any fractionation schedule. A detailed protocol is given for rat liver because of the widespread use of this tissue. Although this technique should be broadly applicable to any soft tissue and to any subsequent fractionation procedure, there are certain tissues and applications that require either minor or extensive modification. Some of these points are addressed in the Notes section.